2014
DOI: 10.1021/es4050083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Enterococcus Species and Their Virulence Genes in Fresh Water Prior to and after Storm Events

Abstract: Enterococcus spp. isolates (n = 286) collected from six surface water bodies in subtropical Brisbane, Australia, prior to and after storm events, were identified to species level and tested for the presence of seven clinically important virulence genes (VGs). Enterococcus faecalis (48%), Enterococcus faecium (14%), Enterococcus mundtii (13%), and Enterococcus casseliflavus (13%) were frequently detected at all sites. The frequency of E. faecium occurrence increased from 6% in the dry period to 18% after the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
(159 reference statements)
2
18
0
Order By: Relevance
“…Several studies have focused on enterococci isolates from surface water (Sidhu et al 2014;Michael et al 2013) and from the environment to achieve a greater understanding of the origin, spread, and persistence of antibiotic-resistant enterococci. However, data about antibiotic-resistant enterococci from Balkan Peninsula surface waters are still unavailable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on enterococci isolates from surface water (Sidhu et al 2014;Michael et al 2013) and from the environment to achieve a greater understanding of the origin, spread, and persistence of antibiotic-resistant enterococci. However, data about antibiotic-resistant enterococci from Balkan Peninsula surface waters are still unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…Enterococci are not indigenous to water and their prevalence in water sources depends on environmental factors including the geographical area, potential sources and types of sewage, and the presence of industrial zones and agricultural sites (Sidhu et al 2014). Detailed studies of individual locations are necessary in order to understand the distribution of Enterococcus species and provide useful information about the dissemination of resistance genes into surface water (Di Cesare et al 2014;Niederhausern et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our findings regarding virulence genes, Rathnayake et al (2012) noticed the presence of esp and gelE genes in E. faecalis and E. faecium water isolates. Recently, gelE, efaA, ace and asa1 genes were reported to occur in Enterococcus isolates from surface waters (Sidhu et al, 2014). A study made by Messi et al (2006) suggested that 3 (0.7%) isolates from superficial waters belonged to the vanA, 53 (13.7%) to the vanB and 43 (11.1%) to the vanC phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Enterococcal surface protein, encoded by the esp gene has been related contributing with colonization of urinary tract, and biofilm formation. The collagen-binding protein gene, ace, is involved in attachment and colonization of renal tissue in animal models (Sidhu et al, 2014). The aggregation substance (agg) takes a part on adhesion to eucaryotic cells and extracellular matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation